2016
DOI: 10.1007/s00405-016-4321-x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of IP and risk of malignant transformation in the Swedish population 1960–2010

Abstract: The true incidence of inverted papilloma (IP) is not yet known. From hospital-based studies, its incidence has been estimated to approximately 0.5/100,000 person years. Earlier hospital case studies have shown that IP can undergo a malignant transformation in 1–53 %. The frequency of its malignant transformation on a population basis is unknown. To our knowledge, no standardised incidence ratio (SIR) has been reported for malignancies among IPs. This study aims to investigate these incidences on a population b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…Sinonasal inverted papilloma (SNIP), as one of the most common benign sinonasal tumors, is characterized by its recurrence tendency, destructive capacity and malignant-transformation possibility (1)(2)(3)(4) . It is well known that the recurrence is mainly caused by incomplete removal of the SNIP (5) , and thus, complete surgical resection, especially the origin of the lesion, is essential for long-term control (3,(5)(6)(7)(8)(9) .…”
Section: Introductionmentioning
confidence: 99%
“…Sinonasal inverted papilloma (SNIP), as one of the most common benign sinonasal tumors, is characterized by its recurrence tendency, destructive capacity and malignant-transformation possibility (1)(2)(3)(4) . It is well known that the recurrence is mainly caused by incomplete removal of the SNIP (5) , and thus, complete surgical resection, especially the origin of the lesion, is essential for long-term control (3,(5)(6)(7)(8)(9) .…”
Section: Introductionmentioning
confidence: 99%
“…In a Swedish population-based study, it was shown that the incidence of SIP has increased from 0.01 to 0.33/100,000 person-years from 1960 to 2010 [14]. Also, the risk of squamous-cell carcinomas in the SIP cohort is significantly higher than in the general population, with a 300-fold increase among male patients with SIP.…”
Section: Discussionmentioning
confidence: 99%
“…El seguimiento estrecho en consulta y la exploración endoscópica periódica pueden disminuir la recurrencia y evitar, de este modo, la malignización [24]. Nuestro estudio está exento de carcinomas, coincidiendo con numerosos artículos publicados [5,[25][26][27][28][29]. Podría asociarse con una mayor tasa de malignización un diagnóstico tardío, un retraso en el tratamiento o diferentes subtipos de papilomas [1,30].…”
Section: Discussionunclassified